2015
DOI: 10.1002/anie.201507122
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Synthesis of N‐Heterocycles by Catalyst‐Controlled, Activity‐Directed Tandem Annulation of Diazo Compounds with Amino Alkynes

Abstract: A stereodivergent synthesis of five-membered N-heterocycles, such as 2,3-dihydropyrroles, and 2-methylene and 3-methylene pyrrolidines, has been developed through a tandem annulation of amino alkynes with diazo compounds and involves the trapping of in situ formed intermediates. Mechanistic investigations indicate that the copper-catalyzed tandem annulations proceed by allenoate formation and subsequent intramolecular hydroamination. In contrast, the rhodium-catalyzed protocol features a carbenoid insertion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 77 publications
(31 reference statements)
1
39
0
Order By: Relevance
“…[9] Many routes for the de novo construction of these 5-membered heterocyclic rings are based on carbene and metallocarbene intermediates, and give a range of functionalized pyrrolidines through cyclization by intramolecular carbene insertion into N-H, [10] or C-H bonds, [11] and related methods continue to be developed. Thus, Sun and co-workers have reported the stereodivergent synthesis of Nheterocycles from the copper(I) or rhodium(II) catalyzed reaction of diazo compounds and amino alkynes, [12] and Hu and co-workers have described the synthesis of pyrrolidines from the intramolecular trapping of transient ylides (Scheme 1).…”
Section: Stereoselective Synthesis Of Functionalized Pyrrolidines By mentioning
confidence: 99%
“…[9] Many routes for the de novo construction of these 5-membered heterocyclic rings are based on carbene and metallocarbene intermediates, and give a range of functionalized pyrrolidines through cyclization by intramolecular carbene insertion into N-H, [10] or C-H bonds, [11] and related methods continue to be developed. Thus, Sun and co-workers have reported the stereodivergent synthesis of Nheterocycles from the copper(I) or rhodium(II) catalyzed reaction of diazo compounds and amino alkynes, [12] and Hu and co-workers have described the synthesis of pyrrolidines from the intramolecular trapping of transient ylides (Scheme 1).…”
Section: Stereoselective Synthesis Of Functionalized Pyrrolidines By mentioning
confidence: 99%
“…C. J. Moody and co-workers elaborated an efficient way for the synthesis of pyrrolidines by trapping of ammonium ylides with ketones [13], whereas J. Sun and colleagues showed that similar reactions can be extended to compounds with triple bonds and allene fragments [14]. …”
Section: Introductionmentioning
confidence: 99%
“…These compounds are prepared from β-ketoesters via diazo transfer reactions 1 and are valuable intermediates in the synthesis of heterocyclic systems, notably including the synthesis of carbapenems as shown in Scheme 1. 2 The stabilized diazo group is capable of selective, and directed, activation with transition metals, including Rh II , especially Rh 2 (OAc) 4 and Rh 2 (esp) 2 , 3 Cu I , 4 Cu II , 5 Ru II , 6 as well as Rh III , 7 Ir III , 8 and Co III , 9 to affect a wide array of intramolecular and intermolecular insertion reactions (N-H, 10 O-H, 11 and C-H 12 ) and addition of the carbenoid to alkenes. 13 The diazo functionality is also susceptible to strongly electrophilic reagents under non-catalytic, conditions, including reactions with bromine and dimethyldioxirane, as shown in Scheme 2.…”
Section: Introductionmentioning
confidence: 99%